Endometrial receptivity and embryo implantation in carnivores—commonalities and differences with other mammalian species. Issue 4 (7th January 2021) - Paulson, Erika Elinor; Comizzoli, Pierre
Abstract: Endometrial receptivity and embryo implantation processes are a major point of pregnancy failure in many mammalian species, including humans. Although reproductive biology in many carnivore species remains enigmatic, the few that have been studied so far are invaluable comparative models. The goals of this review are to (1) summarize current data on the mechanisms involved in uterine receptivity and embryo implantation in carnivores, including commonalities and differences with other mammalian species and (2) identify research priorities to better understand a key phenomenon in a critical group of mammals. Besides unique reproductive traits in some carnivores (induced vs. spontaneous ovulation in cats, ovulation at the germinal vesicle stage in dogs), preimplantation embryo development is comparable with other orders. However, the timing of implantation varies, especially in species having an embryonic diapause. Mechanisms involved in endometrial receptivity and decidualization still remain to be fully understood, but specific markers have already been identified. Importantly, the use of endogenous hormones to control the ovarian activity may impact endometrial receptivity and subsequent embryo implantation. Next, research efforts should take advantage of advanced technologies to further study embryo implantation in carnivores and to provide more relevant models to reproductive medicine or for the conservation of rare and endangered species. Abstract : The goals of this review are to (1) summarize current data on the mechanisms involved in uterine receptivity and embryo implantation in carnivores and (2) identify research priorities to better understand a key phenomenon in a critical group of mammals.